(untitled) (JS (JURNAL SEKOLAH), 2019)
Abstract: Efforts to Improve Indonesian Language Learning Outcomes Through the Application of Meaningful Group Work Methods to Class VII Students of SMP Merdeka 1 Gunung Meriah. The subjects of this study were 23 grade VII students. The results showed that the application of group work methods could significantly improve student learning outcomes for Indonesian subjects, this can be seen from the acquisition of final test scores that out of the 23 students who took the test, there were 5 students who received scores with a percentage ranging between 85 -100 or 21.7% criteria very well, 11 students get scores with percentage ranges between 70-84 or 47.8 of the number of students, 7 students get scores with percentage ranges between 50-69 or 30.5% of the total students, classical absorption 75.5%. Keywords: learning outcomes, and group work methods Abstrak: Upaya Peningkatan Hasil Belajar Bahasa Indonesia Melalui Penerapan Metode Kerja Kelompok Bermakna Pada Siswa Kelas VII SMP Negeri 1 Gunung Meriah. Subjek penelitian ini adalah siswa kelas VII sebanyak 23 orang. Hasil penelitian menunjukkan bahwa penerapan metode kerja kelompok bermakna dapat meningkatkan hasil belajar siswa terhadap mata pelajaran Bahasa Indonesia, hal ini dapat dilihat dari perolehan nilai tes akhir bahwa dari 23 orang siswa yang mengikuti tes, terdapat 5 orang siswa yang memperoleh skor dengan persentase rentang antara 85-100 atau 21,7% kriteria baik sekali, 11 orang siswa memperoleh skor dengan persentase rentang antara 70-84 atau 47,8 dari jumlah siswa, 7 orang siswa memperoleh skor dengan persentase rentang antara 50-69 atau 30,5% dari jumlah siswa, daya serap klasikal 75,5%. Kata kunci: hasil belajar, dan metode kerja kelompok